The Role and Function of the Articles of Association as a Pillar of Cooperative Member Welfare - Niswah Azranillah; Devi Auliya Putri; Mashudi (Penerbit Hellow Pustaka, 2025)
Cooperatives play a strategic role in supporting the development of a people-centered economy by improving the welfare of their members. The success of a cooperative is largely determined by a strong legal foundation and transparent, accountable organizational governance, as embodied in the Articles of Association (AD) and Bylaws (ART). This study aims to analyze the role and function of AD/ART in enhancing the welfare of cooperative members. A descriptive qualitative approach was used, gathering data from various relevant sources. The results show that AD/ART not only serves as a formal administrative guide but also plays a crucial role in regulating the cooperative's operational mechanisms, safeguarding members' rights and obligations, and encouraging active participation in decision-making and business management. Consistent implementation of AD/ART can prevent internal conflicts, improve organizational accountability, and ultimately support the achievement of the cooperative’s main goal: sustainable improvement of its members' welfare